(untitled) (Altre Modernità, 2022)
State authoritarianism appears deeply rooted in Brazilian society and is part of a paradoxical scenario in which the expansion of political rights is accompanied by a substantial delegitimization of civil rights. This authoritarian legacy, repudiates the subalterns and perpetuates their humiliation, targeting the poorest segments of the population, who incessantly suffer various forms of violence by the police and, in general, by the judicial system. Brazilian literature, or at least part of it, can be, however, considered a great archive of non-hegemonic counter-narratives, which pose as a critical consciousness of an unequal modernization and the violence of the processes of domination that characterize it. In this perspective, the article analyzes some short stories present in the collection O sol na cabeça (2018) by Geovani Martins, an emerging writer who traces in his work a meticulous portrait of the life of morros, recounting the tyranny of organized crime, but especially police violence, in a perspective that highlights, in the protection of order by the Brazilian state, an "excess of negativity" (Han) based on a logic of “torture” (Foucault).